Business intelligence : a managerial approach - Turban, Efraim; Sharda, Ramesh; Delen, Dursun; King, David; Aronson, Janine E. (Boston : Prentice Hall, 2018)
For courses on Business Intelligence or Decision Support Systems.A managerial approach to understanding business intelligence systems.To help future managers use and understand analytics, Business Intelligence provides students with a solid foundation of BI that is reinforced with hands-on practice
An overview of Business Intelligence, Analytics, and Data Science --Descriptive Analytics I: Nature of Data, Statistical Modeling, and Visualization --Descriptive Analytics II: Business Intelligence and data Warehousing --Predictive Analytics I: Data Mining Process, Methods, and Algorithms --Predictive Analytics II: Text, Web and Social Media Analytics --Prescriptive Analytics: Optimization --Big Data Concepts and Tools --Future Trends, Privacy and Managerial Considerations in Analytics.
Includes bibliographical references and index.
Keywords: Business intelligence; Industrial management